2020
DOI: 10.1111/iej.13329
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of TLR2‐mediated periapical inflammation

Abstract: AimTo determine the methylation pattern of TLR2 gene promoter and its association with the transcriptional regulation of periapical inflammatory and angiogenic responses in symptomatic and asymptomatic forms of apical periodontitis.MethodologyIn this cross‐sectional study, apical lesions were obtained from volunteers with asymptomatic apical periodontitis (AAP) (n = 17) and symptomatic apical periodontitis (SAP) (n = 17) scheduled for tooth extraction, and both total RNA and DNA were extracted. DNA was bisulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Emerging evidence supports that DNA methylation can also act by regulating the binding of transcription factors (TF) or methyl-CpG-binding proteins in a CpG site-specific manner (52)(53)(54). Particularly in ALEOs, unmethylated CpG single-sites -10 and -12 are associated with transcriptional upregulation of TLR2 (10). Interestingly, these CpG single-sites are close to the NFkB binding sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence supports that DNA methylation can also act by regulating the binding of transcription factors (TF) or methyl-CpG-binding proteins in a CpG site-specific manner (52)(53)(54). Particularly in ALEOs, unmethylated CpG single-sites -10 and -12 are associated with transcriptional upregulation of TLR2 (10). Interestingly, these CpG single-sites are close to the NFkB binding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction TLR2-ligand activates intercellular signaling that induces nuclear factor κ -B (NF κ B) translocation to the nucleus and the consequent inflammatory cascade activation ( 9 ). The expression of TLR2 can be regulated by transcriptional changes that depend on epigenetic modifications in ALEOs ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study group has previously demonstrated that the expression of toll-like receptors (TLR)-2 and -4, which are involved in the recognition of damage and pathogen molecular patterns, were positively correlated with VEGF-A in human ALEOs. In the same study, mRNA levels of VEGF-A were detected in both, asymptomatic and symptomatic AP [67]. The detection of VEGF-A in both clinical entities is related to its role in endothelial cell proliferation associated with chronic inflammation, apparently without participation in the clinical exacerbation of the disease.…”
Section: Apical Periodontitismentioning
confidence: 65%
“…The detection of VEGF-A in both clinical entities is related to its role in endothelial cell proliferation associated with chronic inflammation, apparently without participation in the clinical exacerbation of the disease. Instead, the symptoms might be mediated by other cytokines and angiogenic factors, like IL-6, TNF-α and CDH5, which were significantly higher in symptomatic compared to asymptomatic AP [67].…”
Section: Apical Periodontitismentioning
confidence: 92%
“…•Methylation is related to gene silencing (82). Hypomethylation of TLR2 promoter exacerbates periapical inflammatory and angiogenic responses in association with symptomatic apical periodontitis (83).…”
Section: Radicular Cystmentioning
confidence: 99%